The encounter of cultures in the work of González Prada (Revista de Crítica Literaria Latinoamericana, 2016)
This article analyzes the issue of the encounter of cultures and their interaction in the Peruvian writer Manuel González Prada’s essays. In his work, the concept of opposition of two until then incompatible cultures is evident: the indigenous and the creole society, that is, the original civilization and the society established based on the European tradition. González Prada opposed the ideas of the French sociologist Gustave Le Bon and his concept of historical races, and he defended not only the indigenous or Peruvian culture, but also the Latin American culture in general. In this way he adopted the problematic methodology of cultural relativism, which is incompatible with the idea of migration and mestizaje.
Keywords: Gonzalez Prada; indigenous people; race; culture; tradition; society